The Effect Of Reading Aloud Strategy To The Students’ Pronunciation Abiity For Grade Seven Of SMP Negeri 3 Pematangsiantar - Mikhael Latin Ahasweros Siahaan; Seviana Napitupulu; Tiarma Intan Marpaung (Jurnal Ilmu Pendidikan dan Sosial, 2024)
The purpose of this research is to find out the effectiveness of students’ pronunciation abiity that was taught by using reading-aloud strategy. The research method that used in this research was a quantitative method, and the research design was quasi-experimental. There are two groups that involve in this research, the experimental class and the control class where each class has given a pre-test and post-test. The sampling technique used is purposivey sampling technique, the sample used in this research consisted of two classes, namely VII-1 as the experimental class were consist of 32 students and VII-2 as the control class were consist of 32 students at SMP Negeri 3 Pematangsiantar. Thus, the total of the sample used by researcher was 64 students. The sample was choose as experimental class has a reading – aloud strategy as a treatment in their class. Thus, control class was taught by applying the conventional method. In the data analysis, the data was obtained through students’ prinunciation in reading a text that contains 25 (twenty five) regular verb in past tense. It was taken after the researcher taught the reading skills to the experimental group by using the Reading Aloud Strategy and the conventional teaching to the control group. The students mean score in pretest at experimental class was 62.96 and the student mean score in the pos-test was 81.13. whie, the mean students in pre-test at control class was 62 and the post -test was 77.7. the researcher found after calculating the t-test formula, t-test is higher than t-table (t-test 2.2 > t-table 1.672). It can be concluded that Ha was accepted and H0 was rejected. For the conclusion Reading-aloud strategy had a significant effect on students’ pronunciation for grade seven students at SMP Negeri 3 Pematang Siantar. Therefore.reading-aloud strategycan be used as teaching strategi on student pronunciation on grade seven students.